The role of human paraoxonase 1 (PON-1) in viral infections - Neves, Nuno de Sousa Paulino (2016)
According to the World Health Organization, Human Immunodeficiency Virus, Hepatitis B virus and Hepatitis C virus are one of the most common causes of chronic viral related disease. The Paraoxonase-1enzyme is a calcium-dependent enzyme associated to high density lipoprotein, with various activities, including paraxaonase, arylesterase and lactonase. This ability to hydrolase various subtracts seems to give the enzyme antioxidant properties and sensibility to oxidative stress. This review cross references the information of most of the recent and available studies done in the area and tries to demonstrate the connections and the importance of the Paraoxonase-1 enzyme that could provide invaluable clinical information. Several studies conclude that significant alterations occur on the enzymatic activity of Paraoxonase-1 in Human Immunodeficiency Virus, Hepatitis B virus and Hepatitis C virus infected patients. This modifications seem to occur due to the increased levels caused by the infections on the organism, leading to multiple disruption on antioxidant and anti-inflammatory pathways that were demonstrated to involve Paraoxonase-1. Although Paraoxonase-1 activity alterations seem to be caused by malignant causes, positive and useful clinical information might be extracted by measuring such alterations. Paraoxonase-1 possibly will be used with more research in future as a biomarker for some viral infections.